Reactions of nitroxides XIII: Synthesis of the Morita–Baylis–Hillman adducts bearing a nitroxyl moiety using 4-acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl as a starting compound, and DABCO and quinuclidine as catalysts - Zakrzewski, Jerzy (Beilstein Journal of Organic Chemistry, 2012)
The Morita–Baylis–Hillman adducts bearing a nitroxyl moiety were synthesized from 4-acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl and aliphatic, aryl and heterocyclic aldehydes.
Keywords: 4-acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl; DABCO; Morita–Baylis–Hillman reaction; nitroxides; quinuclidine